Evaluation of Glucose Response to 3 Types of Insulin Using a Continuous Glucose Monitoring System in Healthy Alpacas. (25th June 2014) - Byers, S.R.; Beemer, O.M.; Lear, A.S.; Callan, R.J.
<x xml:space="preserve">Abstract</x> Background Persistent hyperglycemia is common in alpacas and typically requires insulin administration for resolution; however, little is known about alpacas' response to different insulin formulations. Objectives To evaluate the effects of 3 insulin formulations on blood glucose concentrations and the use of a continuous glucose monitoring (CGM) system in alpacas. Animals Six healthy alpacas. Methods The CGM was installed in the left paralumbar fossa at the start of this crossover study and recorded data every 5 minutes. Regular insulin, NPH insulin, insulin glargine, and dextrose were administered to each alpaca over a 2‐week period. Blood samples were collected for glucose testing at 0, 1, 2, 4, 6, 8, and 12 hours, and then every 6 hours after each administration of insulin or dextrose. Data were compared by using method comparison techniques, error grid plots, and ANOVA. Results Blood glucose concentrations decreased most rapidly after regular insulin administration when administered IV or SC as compared to the other formulations. The NPH insulin produced the longest suppression of blood glucose. The mean CGM interstitial compartment glucose concentrations were typically lower than the intravascular compartment glucose concentrations. The alpacas had no adverse reactions to the different insulin formulations. Conclusions and Clinical Importance The NPH insulin might be more appropriate for long‐term use in hyperglycemic alpacas because of its extended duration of action. A CGM is useful in monitoring glucose trends and reducing blood collection events, but it should not be the sole method for determining treatment protocols.